Role of Artificial Intelligence in Creating Excellence in Entrepreneurship: A Literature Review - Gaurav, Kumar; Mahato, Jogeswar (Indian Journal of Computer Science, 2023)
Artificial Intelligence (AI) is a digitally controlled robot or computer function that performs human activities. It has a significant impact on the prospects of entrepreneurial activities in a business circumstance. Artificial Intelligence has made it easier to reach a specific audience by recognising patterns in how people search and by giving them the information they need. Because of the growth of automation and Artificial Intelligence (AI), new ways of running a business are coming up. There isn’t a lot of study on how digitalisation and entrepreneurship work together. So, the present study aims to learn more about this area and gives a semantic analysis of the contributions of Artificial Intelligence in the areas of entrepreneurship. Based on the results, it is clear that AI helps managers hire the right people for the job by analysing a potential of candidates based on their interests and past work experience and choosing the right person for the job. It also helps find risks, and protects companies from cyber attacks, keeps systems organised, and ensures everything works well. It protects the business infrastructure by recognising cyber threats from data by looking for trends.